Imaging Features of the Juvenile Inflammatory Arthropathies - Sudoł-Szopińska, Iwona; Jans, Lennart; Jurik, Anne Grethe; Hemke, Robert; Eshed, Iris; Boutry, Nathalie (Seminars in Musculoskeletal Radiology, 2018)
We discuss the imaging of several juvenile inflammatory arthropathies including juvenile idiopathic arthritis, juvenile systemic lupus erythematosus, juvenile scleroderma, juvenile dermatomyositis, and chronic recurrent multifocal osteomyelitis. Juvenile idiopathic arthritis is the most common autoimmune chronic systemic disease of connective tissue in children. The remaining systemic juvenile connective tissue diseases are rare. However, they require early diagnosis and initiation of treatment to prevent injury, not only to the musculoskeletal system but also to the internal organs, and even death. Imaging of juvenile inflammatory arthropathies has relied for years on radiography. Recent advances in disease-modifying drugs have led to a greater emphasis on the detection of early inflammation not evident on plain radiography. Ultrasound examination allows for the early recognition of the disease process in the soft tissues. Magnetic resonance imaging detects early inflammatory changes involving the soft tissues, the subcortical bone of peripheral joints, the spine, and entheses.
Keywords: juvenile idiopathic arthritis; juvenile systemic lupus erythematosus; juvenile scleroderma; juvenile dermatomyositis